Appropriate lightweight cryptosystems for wireless sensor networks - Kasra-Kermanshahi, S. (2016)
The nature of constrained resources of sensor nodes, beside of the inherent vulnerability, led to proposing many lightweight cryptosystems in Wireless Sensor Networks. In this paper, we have traced the use of appropriate cryptosystems for wireless networks and covered different cryptographic protocols of main primitives, which are Encryption, Digital Signature and Key Agreement. Our unique integrated categorization of the proposed lightweight cryptosystems would be useful for those cryptologists who are developing lightweight and applicable schemes for Wireless Sensor Networks.